From the heteronomy of the technological project to the evolutionary hybridization of the experimental research - Calzolari, Marta; Pietromaria Davoli; Luisa Dias Pereira (TECHNE - Journal of Technology for Architecture and Environment, 2021)
The growing complexity of the construction process, pressured by challenges related to safety, climate change and the reduction of energy consumption, requires the ability to manage more and more skills previously allocated exclusively to other specialists. It is therefore necessary to establish a dialogue based on advanced collaborative designs, which lead to an increase in the adequacy of the design response. The HeLLo MSCA IF Horizon2020 research exemplifies how technological leadership controlled the objectives and final outcomes of a highly interdisciplinary experimental study. Concerning the EU priorities, the research has created hybridization between environmental design, conservation and physical-technical aspects including the dissemination of the project results.